Renormalized solutions in thermo-visco-plasticity for a Norton–Hoff type model. Part I: The truncated case. (April 2016) - Chełmiński, Krzysztof; Owczarek, Sebastian
Abstract: We prove existence of global in time strong solutions to the truncated thermo-visco-plasticity with an inelastic constitutive function of Norton–Hoff type. This result is a starting point to obtain renormalized solutions for the considered model without truncations. The method of our proof is based on Yosida approximation of the maximal monotone term and a passage to the limit.